Dark Sky Collaborators: Arizona (AZ) Observatories, Communities, and Businesses. (5th March 2015) - del Castillo, Elizabeth Alvarez; Corbally, Christopher; Falco, Emilio E.; Green, Richard F.; Hall, Jeffrey C.; Williams, G. Grant
Abstract: With outdoor lighting ordinances in Arizona first in place around observatories in 1958 and 1972, then throughout the state since 1986, Arizonans have extensive experience working with communities and businesses to preserve our dark skies. Though communities are committed to the astronomy sector in our state, astronomers must collaborate with other stakeholders to implement solutions. Ongoing education and public outreach is necessary to enable ordinance updates as technology changes. Despite significant population increases, sky brightness measurements over the last 20 years show that ordinance updates are worth our efforts as we seek to maintain high quality skies around our observatories. Collaborations are being forged and actions taken to promote astronomy for the longer term in Arizona.